Teacher’s Nonverbal Immediacy Behaviour in Senior High School - Wijaya, Rendra Kusuma; Nurhayana, Ince (Jurnal Ilmiah Multidisiplin Amsir, 2025)
Nonverbal communication in the classroom is as essential as verbal interaction in shaping effective teaching and learning. This study explored students’ perceptions of their English teacher’s nonverbal communication in class XI IPS 2 at SMAN 1 Pangale. The findings indicate that the teacher demonstrated effective nonverbal immediacy, which included neat and professional appearance, meaningful eye contact, supportive gestures, and frequent smiling. These behaviors contributed to creating a positive classroom atmosphere where students felt more comfortable, relaxed, confident, and engaged in the learning process. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The study population comprised students from classes XI IPS 1 and XI IPS 2, with a sample of 25 students from XI IPS 2. The results highlight the significant role of nonverbal communication in enhancing students’ motivation, comprehension, and overall classroom participation.